PELATIHAN PENYUSUNAN LAPORAN KEUANGAN BAGI BUMDES DI KECAMATAN CIJULANG - Irman Firmansyah; R. Neneng Rina Andriani; Rani Rahman; Kurniawan kurniawan (Universitas Pendidikan Indonesia, 2023)
The purpose of community service activities in the Community Service Scheme (PbM-KT) scheme is for Village-Owned Enterprises (BUMDES) located in Cijulang Village, Pangandaran Regency, especially in BUMDES GUHA BAU Kertayasa Village. The importance of preparing good financial reports for BUMDES is a form of financial management accountability received by BUMDES from the Village Government and from other parties including accountability to the community. The problem raised is the lack of human resources who are able to prepare BUMDES financial reports properly. Usually, BUMDES financial managers are employees who do not have special skills, especially standardized financial accounting. Thus, special training is needed so that the preparation of BUMDES financial reports, especially those who are partners, will be able to manage finances well so that financial reports will be made properly as well. The method of solving community service problems is to conduct training to partners in preparing financial reports. The training is carried out directly to the BUMDES management regarding the preparation of BUMDES financial statements that are in accordance with the Private Entity Financial Accounting Standards (SAK-EP) but are prepared easily. Therefore, we use an application called SIADES (BUMDES accounting information system) which was deliberately created for this program. The results of the activity show that the BUMDES financial manager is greatly facilitated by the use of this application because the work can be done quickly and precisely.